Impact of Multicultural Diversity on the Gender Stereotyping in Bapsi Sidhwa’s The Pakistani Bride through the Deconstructive Perspective - Muhammad Shakil ur Rehman; Khan, Abdul Hamid (Journal of Peace, Development and Communication, 2020)
The article analyzes the impact of multicultural fictional representation of the two female characters on the gender stereotyping in Bapsi Sidhwa’s The Pakistani Bride (1990) by applying Judith Butler’s gender approach. The novelist (1938) is a distinguishing Anglophone, post-colonial and diaspora writer in South Asia (Suleri, 2001) who is known to be the pioneer of Pakistani novel in English. Sidhwa’s portrayal of different cultural milieu in the novel under study is to highlight the impact on gender identification through the analysis of the performativity of the two brides, Zaitoon and Carol. The first lady, one of the key characters, confronts and challenges the tribal gender norms of a Pakistani society and the second bride mirroring of an American culture projecting of a diverse identification. The multicultural contextual background of the novel leads the debate to analyze how different gender roles are performed by each of the brides to support the research contention that gender is wrought not by sexual categorization but by socio-cultural stereotyping. Therefore, the cultural differences in the book necessarily require fluid shades of gender identification accordingly. It is the targeted objective of the research framework applied by the study that gender is an action, it is a fluid and instable feature as has been manifested through the performance of the focused characters in the novel.